Mean-field Dynamics of Rydberg-Dressed Bosonic Atoms in Free-Space and Optical Lattices - McCormack, Gary (2022)
In the past several decades, cold atom experiments have provided physicists with copious amounts of new discoveries, none more important than that of Bose-Einstein condensation, where laser-cooled bosonic gases `condense' into the lowest available energy state of the system. While playing a pivotal role in ultracold experiments, atoms within a Bose Einstein condensate interact very weakly with one another. A major dichotomy to this is interaction experienced by Rydberg atoms, where the interaction strength between atoms are orders of magnitude larger than standard atom-atom interactions.